Viewing Body Memory Awareness as Self-Reflection - Pratama, I Putu Oka Surya (Journal of Urban Society's Arts, 2024)
The process of self-control abilities contained in a person requires an important role in interaction with other people and the environment in order to form a mature self-control process. This is necessary because researchers try to apply body reflexes to self-control to find an emotional identity that gives rise to awareness, processes a person’s physical, psychological and behavioral traits, in other words a series of processes that shape one’s identity. Demonstrate full awareness of the impact of every action taken to achieve balance and calm in self-control without strong external control. Researchers try to apply the concept of Balinese culture, namely Sad Ripu. The harmony referred to here is the relationship between the elements in a practice. Based on the main Sad Ripu (six enemies) that exist within humans themselves. Researchers try to present it as an entertainment space in the art of dance. Proses kemampuan pengendalian diri yang terdapat pada seseorang memerlukan peranan penting interaksi dengan orang lain dan lingkungannya agar membentuk proses pengendalian diri yang matang, hal tersebut dibutuhkan karena peneliti mencoba menerapkan refleks tubuh pada sebuah pengendalian diri untuk mencari sebuah jati diri terhadap emosional yang memunculkan sebuah kesadaran, proses fisik, psikologis, dan perilaku seseorang, dengan kata lain serangkaian proses yang membentuk jati diri. Memperlihatkan kesadaran penuh akan dampak dari setiap tindakan yang diambil untuk mencapai keseimbangan dan kedamaian dalam pengendalian diri tanpa kendali eksternal yang kuat. Peneliti mencoba menerapkan konsep kebudayaan Bali yakni Sad ripu. Keselarasan yang dimaksud disini adalah bagaimana hubungan antara unsur-unsur yang ada pada sebuah laku. Berdasarkan dari Sad Ripu (enam musuh) utama yang ada di dalam diri manusia itu sendiri. Peneliti mencoba menghadirkan sebagai ruang pertunjukan dalam seni tari.